2023
DOI: 10.3390/nu15030494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Vitamin D Deficiency in Children and Adolescents in the Kingdom of Bahrain

Abstract: Background: Vitamin D deficiency has reached pandemic levels in the Middle East and North Africa (MENA) region, even though sunshine is abundant all year round for the cutaneous synthesis of vitamin D through the skin. This study aimed to determine the prevalence of vitamin D deficiency and risk factors associated with serum 25-hydroxy vitamin D (25(OH)D) in children and adolescents aged from 10 to 19 years, as well as the possible associations of vitamin D with calcium, magnesium and phosphate levels. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Although it is acknowledged in several journals that exposure to sunlight is not the only factor affecting an individual's vitamin D status and levels, UVB sunlight exposure is still necessary for the production of vitamin D, which is regarded as the main source of vitamin D for the majority of the population rather than dietary sources. In addition, a number of variables like air pollution and a number of candidate genes like cytochrome P450 may be involved in the variation in serum vitamin D levels between people [35,40]. Another study on Indonesian children found that the VD deficient group received less sun exposure than the group of VD sufficient, and this finding is consistent with that study's findings [30].…”
Section: Resultssupporting
confidence: 52%
“…Although it is acknowledged in several journals that exposure to sunlight is not the only factor affecting an individual's vitamin D status and levels, UVB sunlight exposure is still necessary for the production of vitamin D, which is regarded as the main source of vitamin D for the majority of the population rather than dietary sources. In addition, a number of variables like air pollution and a number of candidate genes like cytochrome P450 may be involved in the variation in serum vitamin D levels between people [35,40]. Another study on Indonesian children found that the VD deficient group received less sun exposure than the group of VD sufficient, and this finding is consistent with that study's findings [30].…”
Section: Resultssupporting
confidence: 52%